2015
DOI: 10.1016/j.drugpo.2015.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence mother–child reunification for mothers with a history of substance use: A systematic review of the evidence to inform policy and practice in Australia

Abstract: Background: An estimated 60-70% of Australian children in out of home care have a parent with a substance use disorder (SUD). The assessment of a parent's history and needs and the design of supportive interventions, particularly for mothers who are often the primary carers of children, are important considerations in deciding whether or not family reunification is desirable and possible. It is not clear from the research how the needs of families can be best met. There are no systematic reviews that provide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Biological parents must independently attempt to overcome barriers related to access to treatment, long waiting lists, no opportunity for treatment near their place of residence, and a lack of funds for treatment. Doab et al () observe that parents (particularly women) who have formal support in the detoxification treatment process have their custody rights restored more often.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological parents must independently attempt to overcome barriers related to access to treatment, long waiting lists, no opportunity for treatment near their place of residence, and a lack of funds for treatment. Doab et al () observe that parents (particularly women) who have formal support in the detoxification treatment process have their custody rights restored more often.…”
Section: Resultsmentioning
confidence: 99%
“…On a global scale, research regarding the issue of reuniting children from foster care families with their biological families has frequently been undertaken with a very wide scope. Most frequently, researchers have focused on the following aspects: psychological effects of placing a child in foster care, relationships of children in foster care with their biological parents, relationships of children in foster care with their foster parents, relationships of foster parents with the biological parents, the impact of kinship between foster parents and the biological parents on the effectiveness of the reunification process, forms of support for biological parents from foster parents in the reunification process, including biological fathers in the reunification process and its impact on the effectiveness of reunification, factors affecting the effectiveness and permanence of reunification, factors causing absence of permanence of the reunification process, and forms of support for biological families following family reunification, foster parents' abilities to identify parents with potential for positive reintegration (Andersson, 1999;Barber & Delfabbro, 2009;Bellamy, 2008;Brook & McDonald, 2009;Connell et al, 2007;Delfabbro, Fernandez, McCormick, & Ketter, 2014;Doab, Fowler, & Dawson, 2015;Farmer & Wijedasa, 2013;Fernandez & Lee, 2011;Frame, Berrick, & Brodowski, 2000;Harward & DePanfilis, 2007;Landy & Munro, 1998;López, del Valle, Montserrat, & Bravo, 2012;Lutman & Farmer, 2013;Miller et al, 2006;Sanchirico & Jablonka, 2000;Sen & Broadhurst, 2011;Shaw, 2006;Terling, 1999;Vanderfaeillie et al, 2015).…”
mentioning
confidence: 99%
“…Or, they may be returning to unresolved parental problems-parental substance misuse and mental health problems, which frequently contribute to the formation of grandfamilies, are not quickly resolved, and because the probability of relapse is high, careful planning and post-reunification monitoring is necessary (Brook & McDonald, 2009;Carlson et al, 2008;Hayslip et al, 2019;Jedwab et al, 2018). In fact, Doab et al (2015) found that the presence of a mental health disorder among women who misused substances negatively predicted the likelihood of reunification. Other parental issues, including ambivalence or a lack of readiness to resume care of the child, may further compound difficulties associated with reunification and contribute to an unsuccessful outcome (Bellamy, 2008;Carlson et al, 2008;Kimberlin et al, 2009).…”
Section: Factors Associated With Successful Reunificationmentioning
confidence: 99%
“…In contrast, parental risk factors such as drug use, alcohol misuse, and mental health problems were consistently linked with recurrences of child maltreatment (White et al, 2015). Another systematic review focused on factors that impacted reunification rates among mothers with histories of substance use; this review concluded that mothers who used heroin had lower rates of reunification and that many had mental health issues co-occurring with their substance use disorders (Doab et al, 2015) but did not specifically address effective interventions.…”
Section: Research On Successful Reunification Of Familiesmentioning
confidence: 99%